Механизм образования гранул при выделении сажи из водных суспензий - Бабенко С. А.; Высоков Б. И.; Никольский С. М.; Майкова Л. К. (Томск, 1985)
Деп. в ОНИИТЭХим, г. Черкассы, 02.04.1985, № 303-ХП-85.